Weaning and extubation failure in myasthenic crisis: a multicenter analysis - Neumann, Bernhard; Angstwurm, Klemens; Dohmen, Christian; Mergenthaler, Philipp; Kohler, Siegfried; Schönenberger, Silvia; Lee, De-Hyung; Gerner, Stefan Toni; Huttner, Hagen Bernhard; Thieme, Andrea; Steinbrecher, Andreas; Dunkel, Juliane; et al. (Journal of neurology, 2023)
Myasthenic crisis (MC) requiring mechanical ventilation is a serious complication of myasthenia gravis (MG). Here we analyze the frequency and risk factors of weaning- and extubation failure as well as its impact on the clinical course in a large cohort. We performed a retrospective chart review on patients treated for MC in 12 German neurological departments between 2006 and 2015. Weaning failure (WF) was defined as negative spontaneous breathing trial, primary tracheostomy, or extubation failure (EF) (reintubation or death). WF occurred in 138 episodes (64.2%). Older Age (p = 0.039), multiple comorbidities (≥ 3) (p = 0.007, OR = 4.04), late-onset MG (p = 0.004, OR = 2.84), complications like atelectasis (p = 0.008, OR = 3.40), pneumonia (p < 0.0001, OR = 3.45), cardio-pulmonary resuscitation (p = 0.005, OR = 5.00) and sepsis (p = 0.02, OR = 2.57) were associated with WF. WF occurred often in patients treated with intravenous immungloblins (IVIG) (p = 0.002, OR = 2.53), whereas WF was less often under first-line therapy with plasma exchange or immunoadsorption (p = 0.07, OR = 0.57). EF was observed in 58 of 135 episodes (43.0%) after first extubation attempt and was related with prolonged mechanical ventilation, intensive care unit stay and hospital stay (p ≤ 0.0001 for all). Extubation success was most likely in a time window for extubation between day 7 and 12 after intubation (p = 0.06, OR = 2.12). We conclude that WF and EF occur very often in MC and are associated with poor outcome. Older age, multiple comorbidities and development of cardiac and pulmonary complications are associated with a higher risk of WF and EF. Our data suggest that WF occurs less frequently under first-line plasma exchange/immunoadsorption compared with first-line use of IVIG.
Gesehen am 08.07.2024